A case of Moyamoya disease complicated by aHUS in a patient with a history of marginal zone B-cell lymphoma: lightning strikes thrice?. Issue 12 (5th December 2019) - Valle, Ana; Papagermanos, Vassiliki; Wotman, Michael; Shani, Dana
Abstract : Atypical haemolytic uraemic syndrome (aHUS) is a rare, acquired thrombotic microangiopathy, mediated by complement activation, in very sick patients. Moyamoya is similarly a rare disease in which stenosis or occlusion of segment(s) of the anterior cerebral circulation leads to the formation of many thin collaterals. Other reports have described an association between HUS and Moyamoya disease in the paediatric population. However, this case study presents the exceptionally rare presentation of an adult with aHUS and Moyamoya disease in a patient who was treated with rituximab for marginal zone B-cell lymphoma.